Dialogic science-policy networks for water security governance in the arid Americas - Lutz Ley, America N. (2020)
Addressing wicked problems challenging water security requires participation from multiple stakeholders, often with conflicting visions, complicating the attainment of water-security goals and heightening the need for integrative and effective science-policy interfaces. Sustained multi-stakeholder dialogues within science-policy networks can improve adaptive governance and water system resilience. This paper describes what we define as “dialogic science-policy networks,” or interactions -- both in structural and procedural terms -- between scientists and policy-makers that are: 1) interdisciplinary, 2) international (here, inter-American), 3) cross-sectoral, 4) open, 5) continual and iterative in the long-term, and 6) flexible. By fostering these types of interactions, dialogic networks achieve what we call the 4-I criteria for effective science-policy dialogues: inclusivity, involvement, interaction, and influence. Here we present several water-security research and action projects where some of these attributes may be present. Among these, a more comprehensive form of a dialogic network was intentionally created via AQUASEC, a virtual center and network initially fostered by a series of grants from the Inter-American Institute for Global Change Research. Subsequently, AQUASEC has significantly expanded to other regions through direct linkages and additional program support for the International Water Security Network, supported by Lloyd's Register Foundation and other sources. This paper highlights major scientific and policy achievements of a notable suite of science-policy networks, shared practices, methods, and knowledge integrating science and policy, as well as the main barriers overcome in network development. An important gap that remains for future research is the assessment and evaluation of dialogic science-policy networks' long-term outcomes.